“There Are So Many White Roads that One Would Like to Walk!..” Folklorist Professor Bronislava Kerbelytė Is Interviewed by Her Student, Professor Rimantas Balsys - Kerbelytė, Bronislava; Balsys, Rimantas (Tautosakos darbai, 2015)
-